Ispol'zovanie fenomena serdecno-dychatel'nogo sinchronizma dlja ocenki reguljatorno-adaptivnych vozmoznostej organizma junych sportsmenov - Aleksanjanc, G. D. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The purpose of the present research is the definition of an opportunity of use and a degree of informativeness of the results of test on the cardiorespiratory synchronism in the estimation of the current functional condition of an organism of young athletes.